Significance of Inclusive Growth in Development: Examining the Role and Need for Inclusive Growth in Society (Journal of Advances and Scholarly Researches in Allied Education, 2022)
According to World Bank, the term inclusive growth refers to pace and pattern of growth, it isthe speed of economic growth and how far it‟s benefits reaching to the people. Organization forEconomic cooperation and Development explains inclusive growth as economic growth that isdistributed fairly across society and creates opportunity for all. It‟s an impartial allocation of resourceswith benefits for every section of society. Thus inclusive growth means economic growth that createsemployment opportunities and helps in reducing poverty and differences in society. Inclusive Growth isGovernment of India top priority, described it as growth including the “poorest of poor”. But India‟s rankin UNDP‟s human development index is 131st which show a wide gap between pace and pattern ofgrowth in country. The concept of Inclusive Growth was first introduced in 11th five year plan (FYP),whose objective was to achieve growth process, broad based improvement, quality of life and equalopportunity to all. The 12th FYP further took forward these objectives focusing on reducing poverty,improving health and livelihood. This paper focuses on concept of inclusive growth, its need and role inInclusion of society at large.